Implementation of Eye Contact and Imitation to Enhance Expressive Language Development in 6-Year-Old Children - Maharani, Natalia Fitri; Sumanto, Reni Pawestuti Ambari (FKIP - Universitas Riau, 2025)
Language serves as a fundamental cornerstone in early childhood development, enabling children to communicate their needs, emotions, and ideas spontaneously without external coercion. This study is driven by concerns regarding delayed expressive language development in young children who experience difficulties with attention, which may impede their interactive communication abilities. The primary objective of this research is to enhance the expressive language skills of a 6-year-old child through targeted interventions involving eye contact and imitation. The method used was experimental quantitative research with a Single Subject Research (A-B) design, in which expressive language development data were collected through observation and documentation referring to the Standard screening guide for Child Development Achievement Levels and Stimulation of Early Detection and Intervention of Growth and Development to evaluate the subject's language development, then analyzed descriptively simple and presented in graphical form. The findings indicate a significant improvement in expressive language development, with the percentage increasing from 31% to 74% following the implementation of the intervention. Therefore, it can be concluded that the use of eye contact and imitation interventions is effective in enhancing expressive language skills in 6-year-old children experiencing difficulties with attention.